Exploring support strategies and training needs for teachers in navigating illness, bereavement, and death-related challenges in the classroom: a scoping review supporting teachers in classroom grief and loss - Riera-Negre, Laia; Hidalgo-Andrade, Paula; Rosselló, Maria Rosa; Verger, Sebastià (Frontiers in Education, 2024)
This scoping review aimed to examine support strategies teachers can use to address illness, grief, and death in the classroom. A total of 24 scientific articles were analyzed from various databases: Medline (PubMed), SCOPUS, Web of Science, Education Resources Information Center (ERIC), Scielo, Dialnet Plus, ScienceDirect Elsevier, OECD Library, and PsycInfo. These articles were subjected to a rigorous quality analysis process. Through a narrative thematic analysis, six categories emerged: (1) the transformative school as an instrument of change, (2) normalizing illness, bereavement, and death, (3) students with limiting illnesses and their classmates, (4) difficulties and needs, (5) rethinking classroom actions and intervention proposals, and (6) benefits of technology and training needs. The findings of the review encompass a range of proposals and strategies for providing support in the classroom, with a particular emphasis on the use of new technologies, artificial intelligence, and social robotics. These tools are seen as effective means to facilitate remote presence, remote participation, and academic progress for students who are unable to physically attend school. The review also provides practical recommendations to empower teachers with effective strategies for supporting students dealing with illness and bereavement.